Comparative Effects of Various Delivery Methods of Cognitive Behavioral Therapy for Insomnia Among Patients With Cancers: Systematic Review and Network Meta‐Analysis - Chen‐I Lee; Muhammad Amirul Mukminin; Ya‐Wen Jan; Tzu‐Hao Wang; Tsai‐Wei Huang; Hsiao‐Yean Chiu (Psycho-Oncology, 2026)
ABSTRACT Background Insomnia affects 30%–60% of cancer survivors, with around 20% meeting criteria for insomnia disorder. Cognitive behavioral therapy for insomnia (CBTi) is the first‐line treatment, but access is limited by cost and therapist availability, prompting exploration of alternative delivery modes, including digital interventions. Purpose To systematically review and conduct a network meta‐analysis (NMA) of the efficacy of different CBTi delivery methods for managing insomnia in cancer survivors. Methods The PubMed, Embase, CINAHL and Cochrane Library were searched for relevant articles published before September 25, 2025. Only randomized controlled trials of adult cancer patients evaluating the effects of any CBTi delivery mode on subjective sleep outcomes were included. Primary outcome was insomnia severity index (ISI) score; secondary outcomes included sleep onset latency (SOL), wake after sleep onset (WASO), total sleep time (TST), and sleep efficiency (SE). A frequentist random‐effects NMA was conducted. Results Twenty‐two trials involving 2040 participants were included. Compared with treatment as usual (TAU), digital CBTi (dCBTi) demonstrated the largest reduction in ISI scores (MD = −9.70, 95% CI = −10.80 to −8.61), followed by telephone CBTi (MD = −8.74). dCBTi also significantly improved SOL (−30.95 min), WASO (−25.62 min), TST (+31.67 min), and SE (+14.63%). Group CBTi significantly improved SOL (−11.60 min) and WASO (−22.03 min). Meta‐regression analyses identified breast cancer diagnosis as a significant moderator of dCBTi effects on SOL (coefficient = 25.20, p = 0.015) and SE (coefficient = −16.17, p = 0.007). The certainty of evidence ranged from low to very low, primarily because of imprecision and network incoherence. Conclusions dCBTi demonstrated the greatest potential for improving insomnia outcomes among the evaluated CBTi delivery modalities. However, given the low certainty of evidence and the presence of network inconsistency for selected outcomes, these findings should be interpreted cautiously. High‐quality head‐to‐head trials are needed to confirm the comparative effectiveness of different CBTi delivery modalities in oncology populations. Trial Registration The study protocol was prospectively registered on PROSPERO (registration no. CRD42023429081)